Peran Edukasi Dan Sosialisasi Dalam Strategi Pemasaran Ditengah Citra Buruk Perusahaan Pialang Di Mata Masyarakat - Alfian Dwi Ramadhan; Sulastri Irbayuni (jurnal ABDIMAS Indonesia, 2023)
Brokerage companies have long developed in Indonesia, but this development has not been accompanied by a good image. The image of brokers in Indonesia seems bad in society so that Indonesian brokerage companies experience losses in reputation and customer trust, which will ultimately affect the business performance of brokerage companies. This phenomenon was also experienced by PT Victory International Future, one of the official brokers and supervised by Bappebti. It is necessary to identify the key factors that influence this bad image. The expected results will outline various marketing strategies that can be used, including communication that focuses on conveying clear information, education on investments and financial instruments, as well as service to clients that prioritizes transparency. Apart from that, it provides strategy options and suggestions for brokerage companies in an effort to improve the company's image and as a real social contribution to developing public knowledge about finance and improving the financial services sector.